2019
DOI: 10.3329/jemc.v9i1.39901
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Fine Needle Aspiration Cytology in Diagnosis of Tuberculous Lymphadenitis

Abstract: Background: Tuberculosis is still a global health problem. Most common presentation of extrapulmonary tuberculosis is tuberculous lymphadenitis. In our setting, keeping huge burden of tuberculosis in mind, clinicians have to depend on pathological diagnosis of enlarged lymph nodes, i.e., cytomorphology with acid-fast staining in diagnosing these cases so that diagnosis and management of such cases can be initiated quickly. Fine needle aspiration cytology (FNAC) of lymph nodes has been a simple, rapid and cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…Whereas, females are most commonly affected by tubercular lymphadenopathy; the proportion of male to female was 1: 1.93. Our study was shown similar result by some previously published studies by Farooq et al [13] ; Nur et al [14] ; Badge et al [16] and Bhatta et al [17] . In our study, tubercular lymphadenopathy cases are most commonly seen in the age range of 21-30 years accounting 34.11% followed by the age range of 11-20 years accounting to 29.61%, cases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whereas, females are most commonly affected by tubercular lymphadenopathy; the proportion of male to female was 1: 1.93. Our study was shown similar result by some previously published studies by Farooq et al [13] ; Nur et al [14] ; Badge et al [16] and Bhatta et al [17] . In our study, tubercular lymphadenopathy cases are most commonly seen in the age range of 21-30 years accounting 34.11% followed by the age range of 11-20 years accounting to 29.61%, cases.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, tubercular lymphadenopathy cases are most commonly seen in the age range of 21-30 years accounting 34.11% followed by the age range of 11-20 years accounting to 29.61%, cases. Correlate to the past studies that observed by some previous studies, given by Agarwal et al [8] ; Nur et al [14] ; Badge et al [16] and Mainali et al [18] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Fine-needle aspiration (FNA) cytology is minimally invasive and costeffective. It is an outpatient diagnostic procedure, nevertheless, the sensitivity and specificity are variable, in the diagnosis of tubercular lymphadenopathy (4). The Ziehl-Neelsen (ZN) staining technique for acidfast bacilli (AFB) is a simple, cheap, and rapid method.…”
Section: Introductionmentioning
confidence: 99%
“…Tamana E-Nur also reported the same pattern of FNAC having a higher sensitivity and lower specificity. The finding from Tamana E-Nur showed the sensitivity of 79.7% and specificity of 48.1% [ 25 ]. This seems to be lower than the finding from this study.…”
Section: Discussionmentioning
confidence: 99%